Women as Agent of Social Inclusion: Experience of the Women of a Local Belief Community in Salamrejo Village - Komalasari, Dewi (Jurnal Perempuan, 2019)
Minority religious groups are vulnerable towards discrimination and social exclusion. Social exclusion is a multidimensional phenomenon that is closely related to the denial of the enjoyment of civil and political rights as well as economic and socio-cultural rights. Social exclusion also excludes the excluded people from development process in the village. This article discusses the social exclusion experienced by community of local belief’s groups, the Association of Eklasing Budi Murko (PEBM) in Salamrejo village, in Kulon Progo, Special Autonomy of Yogyakarta. The economic empowerment approach has been used to promote inclusion among communities in the village. The establishment of Cooperative Business Group (KUBE) and also other economic works have encouraged women’s role as agent for social inclusion. Business activities established by PEBM have opened room for interaction between women from local belief’s community with other women in the village.